Armodafinil for fatigue associated with menopause: an open-label trial. Issue 2 (February 2016) - Meyer, Fremonta; Freeman, Marlene P.; Petrillo, Laura; Barsky, Maria; Galvan, Thania; Kim, Semmie; Cohen, Lee; Joffe, Hadine
Abstract: Objective: This study aims to obtain preliminary data on the efficacy of armodafinil for improving menopause-related fatigue and quality of life. Methods: Women (aged 40-65 y) experiencing menopause-related fatigue received open-label armodafinil therapy (up to 150 mg/d) for 4 weeks. Changes from baseline in Brief Fatigue Inventory score and Menopause-Specific Quality of Life (MENQOL) physical domain score were examined using the Wilcoxon signed rank test. Exploratory analyses examined the effects of armodafinil on hot flashes, overall quality of life, insomnia, depression, anxiety, and perceived cognitive performance. After open-label treatment, participants were randomized to double-blind continuation of armodafinil versus placebo for 2 weeks to examine whether treatment discontinuation would precipitate symptom recurrence. Results: Of 29 eligible participants, 20 women (69.0%) completed the trial. During treatment with armodafinil (mean dose, 120 mg/d), median Brief Fatigue Inventory scores decreased by 57.7% from 5.2 (interquartile range [IQR], 4.6-6.2) to 2.2 (IQR, 1.1-4.4; P  = 0.0002), and median MENQOL physical domain scores decreased by 51.3% from 3.9 (IQR, 2.3-4.8) to 1.9 (IQR, 1.3-2.7; P  = 0.0001). Median hot flashes for 24 hours decreased by 48.3% from 2.9 (IQR, 1.1-4.6) to 1.5 (IQR, 0.4-2.4; P  = 0.0005). Improvements in MENQOL total score (49%; P  = 0.0001), cognitive function (59.2%; P  = 0.0002), depressive symptoms (64.7%; P  = 0.0006), insomnia (72.7%; P  = 0.0012), and excessive sleepiness (57.1%; P  = 0.0006) were noted. Randomized continuation (n = 10) or discontinuation (n = 10) did not indicate group differences. Armodafinil was well-tolerated; three women (12%) were withdrawn for adverse events. Conclusions: These preliminary results suggest a therapeutic effect of armodafinil on fatigue affecting quality of life during menopause, and a potential benefit for other menopause-related symptoms. Abstract : Supplemental Digital Content is available in the text